A dél-dunántúli gazdasági elit változásai: 1945-1968 - Kaposi, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The previous economic and social elite lost its influence after the World War II. They were chased, sentenced to prison and many of them were tortured to death. The Commun-ist Party’s local members were appointed to be managers of large estates and factories. They were the so called „worker directors". Their tasks were the dismissal of the previous managers and the launch of the planned-economy. Large estates were parceled in 1945. In the ages 1950 the owners of these parceled lands established farmers’ co-operative. Some well-functioning manors were transformed to large state farms. The selection of executives was based on how loyal to the Communist Part they were. Because of these, the produc-tivity of the agriculture and the industry declined.